EXPAND AND EXPLORE STRATEGIC GLOBAL AND REGIONAL NETWORKS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BANDUNG, 14 October 2015 – The Local Knowledge team from Universiti Sains Malaysia (USM) is expanding its role in the area of local knowledge regionally with the organisation of the International Conference on Local Knowledge 2015.